Factors Influencing Birth Preparedness and Complication Readiness Among Childbearing Age: Mixed Methods - Galas, Jerline L.; Vargas-Alvarez, Joleefer L.; Banaticla, Melania S. (Technium Social Sciences Journal, 2025)
Birth preparedness and complication readiness (BPCR) is a crucial intervention aimed at reducing maternal mortality rates. Despite its proven efficacy, numerous barriers impede its effective practice. This study explores the factors influencing BPCR among childbearing age women by assessing the impact of knowledge, preparation, attitude, and practices. Employing a mixed-method research design, data were collected using adapted survey questionnaires and interview guides. The study, conducted in Barangay Bucal, Calamba City, Laguna, involved 33 quantitative and 10 qualitative respondents, totaling 43 childbearing age women from primary health centers. The demographic profile revealed that the majority of respondents were young adults (18-25 years), had secondary education, experienced only one previous birth, and were Roman Catholic. The findings indicated that the respondents’ knowledge, preparation, attitude, and practices related to BPCR were moderate. Statistical analysis revealed that age significantly influenced all four factors—knowledge, preparation, attitude, and practices—while the number of previous births significantly affected attitude and practices. However, civil status, educational attainment, and religion showed no significant impact. Qualitative data highlighted challenges such as transportation difficulties and financial instability as significant barriers to effective care and pregnancy management. The study recommends that childbearing age women pursue formal education to enhance their knowledge and skills, attend antenatal counseling, increase awareness of obstetric complications, rely on faith for support, secure transportation for delivery, strengthen support systems, and develop a structured action plan. These measures aimed to improve BPCR and address the identified barriers, ultimately contributing to reduced maternal mortality rates.